Exploration of alive-and-ventilator free days as an outcome measure for clinical trials of Resuscitative interventions. - Ari Moskowitz; Xianhong Xie; Michelle Ng Gong; Henry E Wang; Luke Andrea; Yungtai Lo; Mimi Kim; Hospital Airway Resuscitation Trial Investigators (PLoS ONE, 2024)
Background Outcome selection is a critically important aspect of clinical trial design. Alive-and-ventilator free days is an outcome measure commonly used in critical care clinical trials, but has not been fully explored in resuscitation science. Methods A simulation study was performed to explore approaches to the definition and analysis of alive-and-ventilator free days in cardiac arrest populations. Data from an in-hospital cardiac arrest observational cohort and from the Pragmatic Airway Resuscitation Trial were used to inform and conduct the simulations and validate approaches to alive-and-ventilator free days measurement and analysis. Findings Alive-and-ventilator-free days is a flexible outcome measure in cardiac arrest populations. An approach to alive-and-ventilator free days that assigns -1 days when return of spontaneous circulation is not achieved provides a wider distribution of the outcome and improves statistical power. The optimal approach to the analysis of alive-and-ventilator free days varies based on the expected impact of the intervention under study on rates of return of spontaneous circulation, survival, and ventilator-free survival. Conclusions Alive-and-ventilator free days adds to the armamentarium of clinical trialists in the field of resuscitation science.